Regional body blocks under ultrasonic control - Kuchin, Iu. L (Pain medicine, 2017)
In this article we have tried to describe the technique of the most used conduction anesthesia of the nerves of the trunk and its purpose. These simple but often underestimated blockades, when used in appropriate operations, provide excellent post-operative analgesia, reduce the need for opioid analgesics, allow the patient to breathe and cough painlessly, and also contribute to early mobilization.